Management and Disclosure of Climate-Related Financial Impacts for State-Owned Enterprises : Toolkit for Shareholders and Regulators - World Bank (Washington, DC, 2022)
The purpose of this Toolkit is to better equip SOE owners and regulators to drive the regulatory,policy, and institutional changes needed to ensure that SOEs consider climate change, integrate it into their operation, and disclose their strategies and actions to address the issue. The Toolkit also provides the boards and executive leadership of SOEs with a framework and guidance on how to understand and respond to the risks and opportunities associated with climate change; to align resources with climate change priorities; and to consider and report on the opportunities, risks, and impacts involved.